MANAJEMEN PERUBAHAN DAN TEKNOLOGI USAHATANI DI KABUPATEN LOMBOK TIMUR - KABUL, LALU MUH. (GANEC SWARA, 2019)
This study discusses management of change, namely changes in farm management that were originally from the use of human labor into the use of technology (tractors) in tillage. The research method used is quantitative. On the one hand the results of the study indicate that there is a change in farm business performance in three components, namely productivity, efficiency and farming costs. On the other hand, technology (tractors) is endogenous, so that it directly affects agricultural production (rice). The development of farmers is not static, but dynamic. For this reason, the technology development strategy is developed from the ideas sof the farmers themselves and is subsequently used as the topic of applied research by various research institutions and the results of such research will then be developed by the private sector into applied technology for farmers.